2017
DOI: 10.3324/haematol.2017.177394
|View full text |Cite
|
Sign up to set email alerts
|

miR-144/451 represses the LKB1/AMPK/mTOR pathway to promote red cell precursor survival during recovery from acute anemia

Abstract: The microRNAs miR-144 and -451 are encoded by a bicistronic gene that is strongly induced during red blood cell formation (erythropoiesis). Ablation of the miR-144/451 gene in mice causes mild anemia under baseline conditions. Here we show that miR-144/451−/− erythroblasts exhibit increased apoptosis during recovery from acute anemia. Mechanistically, miR-144/451 depletion increases the expression of the miR-451 target mRNA Cab39, which encodes a co-factor for the serine-threonine kinase LKB1. During erythropo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(52 citation statements)
references
References 49 publications
7
45
0
Order By: Relevance
“…Thus, in GBM cells, metabolic stress triggers a Cab39/AMPK-mediated positive feedback response between miR-451 and OCT1, which allows tumor cells to quickly adapt to variations of glucose concentrations in the tumor microenvironment. These findings in GBM cells uncover miR-451 as a major player in AMPK signaling, which is consistent with a recent finding in erythroid cells that miR-451 is an important effector that represses Cab39/AMPK activity [46]. The inconsistency is that deficiency of miR-451 in nucleated erythroid cells results in apoptosis, rather than adaptation for survival, in numerous stress conditions, including deprivation of glucose in culture medium ( [46]; unpublished data).…”
Section: Regulation Of Mir-144/451 Expression At Transcriptional Levelssupporting
confidence: 88%
See 2 more Smart Citations
“…Thus, in GBM cells, metabolic stress triggers a Cab39/AMPK-mediated positive feedback response between miR-451 and OCT1, which allows tumor cells to quickly adapt to variations of glucose concentrations in the tumor microenvironment. These findings in GBM cells uncover miR-451 as a major player in AMPK signaling, which is consistent with a recent finding in erythroid cells that miR-451 is an important effector that represses Cab39/AMPK activity [46]. The inconsistency is that deficiency of miR-451 in nucleated erythroid cells results in apoptosis, rather than adaptation for survival, in numerous stress conditions, including deprivation of glucose in culture medium ( [46]; unpublished data).…”
Section: Regulation Of Mir-144/451 Expression At Transcriptional Levelssupporting
confidence: 88%
“…These findings in GBM cells uncover miR-451 as a major player in AMPK signaling, which is consistent with a recent finding in erythroid cells that miR-451 is an important effector that represses Cab39/AMPK activity [46]. The inconsistency is that deficiency of miR-451 in nucleated erythroid cells results in apoptosis, rather than adaptation for survival, in numerous stress conditions, including deprivation of glucose in culture medium ( [46]; unpublished data). Farnesoid X Receptor (FXR) is a nuclear receptor and controls many aspects of lipid metabolism.…”
Section: Regulation Of Mir-144/451 Expression At Transcriptional Levelssupporting
confidence: 88%
See 1 more Smart Citation
“…Results miR-144 suppressed the proliferation of glioma cells. The miRNAs array analysis from several groups indicated that miR-144 and miR-451a, as anti-tumor miRNAs located in the same cluster, were decreased in different tumor tissues and modulated tumor development [20][21][22] . However, the detail mechanism still remains unclear.…”
Section: Ros Generation Detectionmentioning
confidence: 99%
“…Therefore identification glioma-related miRNAs and elucidation their effects and regulatory mechanisms have important roles in gliomas therapy. miR-144 located within the miR-144/miR-451a cluster and plays significant roles in tumor progression [20][21][22] . Several reports indicated that miR-144 could suppress tumor cell proliferation and block the cell cycle [23][24][25] .…”
mentioning
confidence: 99%